The Expectation in ( Why did you leave the horse alone ) By Mahmoud Darwish (Journal of the College of Languages (JCL), 2015)
Expectation in poetry is the ability of the poet to exceed the existence of the universe . It is the revealing of the hidden and the familiar. This feature of expecting is not related to the modern poetry only . It is a well - known feature that has long been assigned to old poetry like Al-Mutannabi an Al-Mu`arri who had their own unique ways of expecting and going beyond the current time and touching the future and making it a reality. Based on their awareness ,mature thinking and talent , they had the ability of reading what is to come ,even if they were mere suppositions and tentative readings. As for the modern poetry , we have poets like Amal Dunqil , Adonis ,and Al-Sayyab whose poems became expectations to the future.In addition to Mahmoud Darwish whose poems are the example of expectation in poetry , especially in his book ( Why did you leave the horse alone) which is more a reading for the future than a book of poems . His book is rich with culture , intuition , rich visions of the future . The eloquence and the images in this book turn to be a reading tool that harness all the possibilities to a better reading for the future ; a better expectation.